Developing an Urban Forest Management Plan for Hurricane-Prone Communities - Francisco Escobedo; Robert Northrop; Wayne Zipperer (EDIS, 2007)
FOR-121, an 11-page full color fact sheet by Francisco Escobedo, Rob Northrop, and Wayne Zipperer, is part of the Urban Forest Hurricane Recovery Program series. It brings together the information and tools from previous fact sheets in this hurricane recovery series, changing the focus to the community rather than the homeowner or arborist and from individual trees to the urban forest. Published by the UF School of Forest Resources and Conservation, September 2007.